Classification of anatomy and treatment approaches for aneurysms originating from the proximal of the A1 segment of the anterior cerebral artery in clinical settings - Liu, Xiao-meng; Song, Xiao-lei; Tang, Kai; Zhang, Chao; Liu, Xiao-song; Zhao, Lei; Wang, Xiao-liang; Du, Hai-long; Hu, Yu-hua; Wu, Jian-liang (Frontiers in Neurology, 2024)
Objective To explore the spatial relationship between A1 segment proximal anterior cerebral artery aneurysms and their main trunks, classify them anatomically and develop targeted treatment strategies. Methods This single-center retrospective analysis involved 39 patients diagnosed with aneurysms originating from the proximal of A1 segment of the anterior cerebral artery (2014–2023). Classify the patient’s aneurysm into 5 types based on the location of the neck involving the carrier artery and the spatial relationship and projection direction of the aneurysm body with the carrier artery, and outcomes from treatment methods were compared. Results Among 39 aneurysms, 18 cases underwent endovascular intervention treatment, including 6 cases of stent assisted embolization, 1 case of flow-diverter embolization, 5 cases of balloon assisted embolization, and 6 cases of simple coiling. At discharged, the mRS score of all endovascularly treated patients was 0, and the GOS score was 5 at 6 months after discharge. At discharge, the mRS score of microsurgical clipping treated patients was 0 for 15 cases, 3 for 1 case, 4 for 1 case and 5 for 2 cases. Six months after discharge, the GOS score was 5 for 16 cases, 4 for 2 cases, 3 for 2 cases, and 1 for 1 case. GOS outcomes at 6 months were better for endovascularly treated patients (p = 0.047). Conclusion Results showed better outcomes for the endovascular treatment group compared to microsurgical clipping at 6 months after surgery. The anatomical classification of aneurysms in this region may be of help to develop effective treatment strategies.